2020
DOI: 10.1111/jcmm.15839
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of ferroptosis protects House Ear Institute‐Organ of Corti 1 cells and cochlear hair cells from cisplatin‐induced ototoxicity

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
44
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(51 citation statements)
references
References 59 publications
0
44
0
Order By: Relevance
“…However, lipid peroxide accumulation is mainly caused by the absence, or insufficient activity, of the selenium peroxidase glutathione peroxidase 4 (GPX4). GPX4 is a unique intracellular antioxidant enzyme that inhibits the production of lipid peroxidation in the cell membrane [ 26 ]. Given that the dynamic balance of iron is intimately linked to the maintenance of human health, disturbances in iron homeostasis can easily lead to a variety of medical conditions [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, lipid peroxide accumulation is mainly caused by the absence, or insufficient activity, of the selenium peroxidase glutathione peroxidase 4 (GPX4). GPX4 is a unique intracellular antioxidant enzyme that inhibits the production of lipid peroxidation in the cell membrane [ 26 ]. Given that the dynamic balance of iron is intimately linked to the maintenance of human health, disturbances in iron homeostasis can easily lead to a variety of medical conditions [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have reported that chemotherapeutic agents can induce ferroptosis in different tumors. Recent studies have shown that ferroptosis inhibitors can reduce the ototoxicity caused by cisplatin 54 . Doxorubicin is a chemotherapy drug commonly used for BRCA, but a common side effect is cardiotoxicity.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have reported that chemotherapeutic agents can induce ferroptosis in different tumors. Recent studies have shown that ferroptosis inhibitors can reduce the ototoxicity caused by cisplatin [51]. Doxorubicin is a chemotherapy drug commonly used for BRCA, but a common side effect is cardiotoxicity.…”
Section: Discussionmentioning
confidence: 99%